1995
DOI: 10.1097/00000539-199508000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthetic Neurotoxicity Does Not Result from Blockade of Voltage-Gated Sodium Channels

Abstract: To investigate whether local anesthetic neurotoxicity results from sodium channel blockade, we compared the effects of intrathecally administered lidocaine, bupivacaine, and tetrodotoxin (TTX), the latter a highly selective sodium channel blocker, on sensory function and spinal cord morphology in a rat model. First, to determine relative anesthetic potency, 25 rats implanted with intrathecal catheters were subjected to infusions of lidocaine (n = 8), bupivacaine (n = 8), or TTX (n = 9). The three drugs produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…However, the three drugs were continuously infused as commercially available solutions but not in equipotent concentrations and, as a result, the lidocaine solution administered was much more potent than the others. Other animal studies (3,9) using equipotent solutions from the same laboratory have revealed no significant difference in functional impairment or morphologic damage among lidocaine and bupivacaine or prilocaine.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…However, the three drugs were continuously infused as commercially available solutions but not in equipotent concentrations and, as a result, the lidocaine solution administered was much more potent than the others. Other animal studies (3,9) using equipotent solutions from the same laboratory have revealed no significant difference in functional impairment or morphologic damage among lidocaine and bupivacaine or prilocaine.…”
mentioning
confidence: 84%
“…In conclusion, although the doses of anesthetics administered were larger than those used clinically, the present results suggest that bupivacaine is less neurotoxic than lidocaine when administered intrathecally at equipotent concentrations in the rat model. I ncreasing laboratory evidence suggests that local anesthetics are potentially neurotoxic and that neurologic impairment after spinal anesthesia may result from a direct neurotoxic effect of local anesthetics (1)(2)(3)(4). Thus, because reported permanent neurologic injury, including cauda equina syndrome, has been associated with lidocaine in most cases (5)(6)(7)(8), this anesthetic may be more neurotoxic than other local anesthetics.…”
mentioning
confidence: 99%
“…Neosaxitoxin should have less cardiovascular and neuronal toxicity than amide local anesthetic, because of its low affinity for sodium channel subtypes expressed by cardiac and brain tissues (Kohane et al 1998;Sakura et al 1995;Catterall 2000). Furthermore, the outer pore blockers had been shown to produce less toxicity on neurons and myocytes (Sakura et al 1995;Padera et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Neosaxitoxin should have less cardiovascular and neuronal toxicity than amide local anesthetic, because of its low affinity for sodium channel subtypes expressed by cardiac and brain tissues (Kohane et al 1998;Sakura et al 1995;Catterall 2000). Furthermore, the outer pore blockers had been shown to produce less toxicity on neurons and myocytes (Sakura et al 1995;Padera et al 2006). Outer pore blockers have been shown, however, to produce systemic toxicity, mainly due to respiratory failure produced by diaphragmatic paralysis, via a direct effect on diaphragm muscle and phrenic nerves, rather than by a central depressing effect (Kao 1972;Kohane et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…When lidocaine, bupivacaine, and tetrodotoxin, a highly specifi c sodium-channel blocker, were intrathecally administered at concentrations ten times each respective anesthetic EC50, lidocaine and bupivacaine induced persistent sensory impairment, whereas tetrodotoxin did not, indicating that local anesthetic neurotoxicity does not result from the blockade of sodium channels [10].…”
mentioning
confidence: 99%